Survey of Capital Market Investment Interest Among Students - Sulaeman, Dede; Hidayah, Dahlan Ibnu; Pratama, Gama; Nyoni, Francis C (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2025)
Although the number of capital market investors in Indonesia continues to increase, capital market penetration is still relatively low, so more intensive education and socialization efforts are needed to encourage public participation, especially the younger generation, in investing. This study aims to determine the effect of motivation, capital market knowledge, and risk preferences on investment interest among students. The type of research used is explanatory with a quantitative approach. The population of the study consisted of students majoring in Islamic economics at Bunga Bangsa University Cirebon who had taken capital market and financial management courses. The sampling technique was carried out using the non-probability sampling method, and data were collected using a questionnaire. The sample of this study was students majoring in Islamic Economics at Bunga Bangsa University Cirebon who had taken investment management and capital markets courses, with a sample size of 30 people. Data collection in this study was carried out through the distribution of questionnaires to students who met certain criteria.The data analysis technique is carried out in a quantitative descriptive manner, where the data collected from the questionnaire will be processed and analyzed to identify trends, patterns, and relationships between the variables studied. The results of the study showed that students had started trying to invest in the capital market. From this study, it is known that the interest of students at Bunga Bangsa University Cirebon in investing is quite high, and the knowledge they gain from capital market courses plays a significant role in increasing their interest in investing.